2008
DOI: 10.1111/j.1520-037x.2007.07320.x
|View full text |Cite
|
Sign up to set email alerts
|

Statin Pretreatment Is Protective Despite an Association With Greater Coronary Artery Disease Burden in Patients Presenting With a First ST‐Elevation Myocardial Infarction

Abstract: The relationship of chronic pre‐event statin use with coronary disease severity at the time of presentation with a first acute ST‐elevation myocardial infarction (STEMI) is unknown. A retrospective review was performed of consecutive patients presenting with STEMI and without a prior history of vascular disease, divided into those whom had been treated with statins before presentation (n=50) and those whom were not pretreated (n=231). Patients pretreated with statins were more likely to have left main (24.0% v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The finding that atherosclerotic burden was higher in patients on statin therapy despite reduced severity of clinical presentation is important for several reasons, Firstly, this finding may imply that statin therapy through plaque-stabilizing effects may have reduced plaque propensity to rupture allowing plaques to reach advanced stages without complications and clinical events. Supporting these views, a higher CAD burden at the time of presentation for STEMI in patients pretreated with statins [31] and a high coronary atherosclerotic burden in asymptomatic patients with familial hypercholeste-rolemia receiving statin therapy [32] have been described. Secondly, higher atherosclerotic burden at the time of presentation may explain the observed shift in the presentation patterns toward more benign clinical forms for at least 2 reasons: first, coronary occlusions at the site of a critical stenosis functionally might be less important than coronary occlusion of mild-to-moderate stenoses because the amount of coronary flow that is interrupted might be already small and, second, critical stenoses might have promoted collateral development which further attenuates the clinical presentation of acute coronary occlusion.…”
Section: Discussionmentioning
confidence: 87%
“…The finding that atherosclerotic burden was higher in patients on statin therapy despite reduced severity of clinical presentation is important for several reasons, Firstly, this finding may imply that statin therapy through plaque-stabilizing effects may have reduced plaque propensity to rupture allowing plaques to reach advanced stages without complications and clinical events. Supporting these views, a higher CAD burden at the time of presentation for STEMI in patients pretreated with statins [31] and a high coronary atherosclerotic burden in asymptomatic patients with familial hypercholeste-rolemia receiving statin therapy [32] have been described. Secondly, higher atherosclerotic burden at the time of presentation may explain the observed shift in the presentation patterns toward more benign clinical forms for at least 2 reasons: first, coronary occlusions at the site of a critical stenosis functionally might be less important than coronary occlusion of mild-to-moderate stenoses because the amount of coronary flow that is interrupted might be already small and, second, critical stenoses might have promoted collateral development which further attenuates the clinical presentation of acute coronary occlusion.…”
Section: Discussionmentioning
confidence: 87%
“…Consistent with our findings, Ndrepepa et al ( 33 ) reported that the atherosclerotic burden was higher in patients under statin therapy. First, patients with higher disease severity prefer to use statins compared to patients with milder conditions; second, this finding may reflect the protective effects of statin therapy: statin pretreatment stabilizes plaques instead of causing rupture, thus avoiding worse outcomes, as previously described ( 34 , 35 ). Notably, subgroup analyses performed based on important baseline characteristics showed the same findings: statin pretreatment was associated with a higher risk of severely obstructive CAD (CADPI ≥ 37) in females, those aged 50 to 75 years, and those with hypertension.…”
Section: Discussionmentioning
confidence: 71%
“…To our dismay, no less than six different units of measure have been used to report troponin, even in recent articles: mg/dl, g/L, g/dl, g/mL, ng/dl, and ng/mL (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Two and sometimes three different units for troponin are used in the same article.…”
Section: E Troponin Units Should Be Unified E To the Editormentioning
confidence: 99%
“…The agents clopidogrel, aspirin, bivalirudin, nickel, paclitaxel, and rapamycin have been incriminated to induce numerous hypersensitivity reactions (2)(3)(4)(5). We have read with interest the very important report published recently in this journal concerning a patient who developed acute multi-vessel coronary stent thrombosis 24 h after uncomplicated implantation of two coronary stents (1).…”
Section: E Troponin Units Should Be Unified E To the Editormentioning
confidence: 99%